Odpowiedź :
a) 4x=8 /:4
x=2. Spr:4 x 2=8
b) -3×=5/:3
-X=1 i 2/3
×=-1 i 2/3. Spr. -3 x -1 i 2/3= 5
c) -3=2x/:2
-1.5=x. Spr. -3=2 x 1.5=-3 = -3
d) 1/4x =1/2 /:1/4
X=2. Spr. 1/4 x 2= 1/2=1/2 =1/2
e) 2/3x =-3/:2/3
x=-4.5 spr. 2/3 x -4.5 = -3
f)212/3=2/3x1:2/3
4=x. Spr. 8/3 = 2/3 x 4
g) 0,2x = 1/:0,2
×=5. Spr. 0,2 x 5 = 1
h) -0,4x=-3/5 /:-0.4
x= 1,5. Spr. -0,4 x 1,5 = -3/5
i) 0,5=-2/3x /:2/3
×=-3/4. Spr. 0,5= -2/3 x-3/4
x=2. Spr:4 x 2=8
b) -3×=5/:3
-X=1 i 2/3
×=-1 i 2/3. Spr. -3 x -1 i 2/3= 5
c) -3=2x/:2
-1.5=x. Spr. -3=2 x 1.5=-3 = -3
d) 1/4x =1/2 /:1/4
X=2. Spr. 1/4 x 2= 1/2=1/2 =1/2
e) 2/3x =-3/:2/3
x=-4.5 spr. 2/3 x -4.5 = -3
f)212/3=2/3x1:2/3
4=x. Spr. 8/3 = 2/3 x 4
g) 0,2x = 1/:0,2
×=5. Spr. 0,2 x 5 = 1
h) -0,4x=-3/5 /:-0.4
x= 1,5. Spr. -0,4 x 1,5 = -3/5
i) 0,5=-2/3x /:2/3
×=-3/4. Spr. 0,5= -2/3 x-3/4
Odpowiedź:
a) 4x=8 /:4
x=2
spr... 4*2=8
8=8
L=P
b) -3x = 5 /:3
x= - 5/3 = - 1 i 2/3
spr... -3 *(-5/3)=5 ( skracamy 3 i 3 przez 3)
-1* (-5)= 5
5=5
L=p
c) -3 = 2x
-3 / : 2= x
-3/2= x
spr... -3= 2*(-3/2) ( skracamy 2 i 2 przez 2)
-3=-3
L=p
d) 1/4 x = 1/2 /:1/4
x= 1/2 *4
x= 4/2=2
spr... 1/4 *2 = 1/2 ( skracamy 4 i 2 przez 2)
1/2 = 1/2
L=p
e) 2/3x = - 3 /:2/3
x= -3 *3/2
x= - 9/2 = - 4 i 1/2
spr... 2/3 *(-9/2) = -3( skracamy 2 i 2 przez 2 , oraz 3 i 9 przez 3)
-3=-3
L=P
Szczegółowe wyjaśnienie: